Is there a place for regional anesthesia in nonoperating room anesthesia?. Issue 4 (August 2020) - Faddoul, Annibal; Bonnet, Francis
Abstract : Purpose of review: General anesthesia and monitored anesthesia care (MAC) are the most widely used techniques in nonoperating room anesthesia (NORA). However, regional anesthesia is slowly finding viable applications in this field. This review aims at providing an update on the current practice of regional anesthesia techniques outside of the operating theatre. Recent findings: Some anesthetic departments have implemented the use of regional anesthesia in novel applications outside of the operating room. In most cases, it remains an adjunct to general anesthesia but is sometimes used as the sole anesthetic technique. The use of the paravertebral block during radiofrequency ablation of different tumors is a recent application in interventional radiology. In emergency medicine, regional anesthesia is gaining traction in analgesia for trauma patients. Summary: Regional anesthesia is finding its way into broader applications every day, offering a range of potential benefits in anesthetic care. Its implementation in NORA is promising and may aid in decreasing patient morbidity. However, great care should be taken in applying the recommended safety precautions for regional anesthesia in any setting.